2020
DOI: 10.3390/jcm10010118
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Perspective for Lung Cancer Characterisation Based on AI Solutions Using CT Images

Abstract: Lung cancer is still the leading cause of cancer death in the world. For this reason, novel approaches for early and more accurate diagnosis are needed. Computer-aided decision (CAD) can be an interesting option for a noninvasive tumour characterisation based on thoracic computed tomography (CT) image analysis. Until now, radiomics have been focused on tumour features analysis, and have not considered the information on other lung structures that can have relevant features for tumour genotype classification, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Nevertheless, the results of the current study indicate that the CT features with the highest correlation with EGFR mutation are from the lung that has the nodule and these are therefore the main contributors to the model decision. It is crucial to highlight these results and further investigate the importance of holistic lung cancer characterization studies, as there are many complex combinations of morphological, molecular, and genetic alterations that occur during lung cancer development that, when taken into account, would allow the development of more accurate classifiers for EGFR mutation status prediction [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the results of the current study indicate that the CT features with the highest correlation with EGFR mutation are from the lung that has the nodule and these are therefore the main contributors to the model decision. It is crucial to highlight these results and further investigate the importance of holistic lung cancer characterization studies, as there are many complex combinations of morphological, molecular, and genetic alterations that occur during lung cancer development that, when taken into account, would allow the development of more accurate classifiers for EGFR mutation status prediction [21].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the nodule is the main focus for lung cancer malignancy assessment and follow-up based on the well-established Fleischner Society and Lung-RADs Guidelines [17,18], and previous studies have analyzed only this important cluster of tumor cells for EGFR mutation status prediction [10,14,16]. Exploratory studies have recently shown that there is a correlation of EGFR mutation status with other lung diseases, such as emphysema and fibrosis, which seems to indicate that cancer development is related to multiple physiological changes not restricted to the nodule region [19,20], and that the inclusion of extratumor features allows a significant increase in EGFR mutation predictive performance [4,5,21].…”
Section: Introductionmentioning
confidence: 99%
“…This structure must be detected, segmented, and assessed to make the initial diagnosis of malignancy. For the malignant cases, CADs could help in cancer characterization, based on more information from the lung structures surrounding the nodules since other lung pathologies are correlated with cancer development [ 69 ].…”
Section: Computer-aided Decision Systemsmentioning
confidence: 99%
“…Exploratory studies that have taken into account features from multiple lung structures, and did not just focus on the nodule, showed the importance of including extra-tumor features to obtain a successful genomic prediction (see Figure 3 , where it is illustrated that radiogenomics approaches use information from more than just the nodule region) [ 50 , 69 , 70 , 71 , 72 , 73 ]. This seems to indicate that cancer development is related to multiple physiological changes not restricted to the nodule region and that the next generation of CADs should consider large lung regions to allow for a more complete lung cancer characterization [ 16 , 74 ].…”
Section: Computer-aided Decision Systemsmentioning
confidence: 99%
“…Deep learning algorithms for classifying and diagnosing lung and colon cancer using histopathology images have become a popular research topic in recent years [39], however, due to a paucity of data, no substantial progress has been achieved so far [40]. Despite the lack of data, a few authors have contributed significantly [41].…”
Section: Related Workmentioning
confidence: 99%